Higher order thinking in social science education: An empirical study with classroom observations from Denmark and Norway - Christensen, Anders Stig; Mathé, Nora Elise Hesby (Sammenlignende Fagdidaktik, 2023)
The aim of this article is to discuss what kinds of higher order thinking are encouraged in social science lessons in lower secondary school. The study used a research design employed by Klette et al. (2017) with video-taped lessons from social science education in Denmark and Norway. We identified teaching segments that included activities promoting higher order thinking and analysed them to produce an overview of the characteristics of cognitively demanding teaching. We found several examples of teaching that encouraged students’ higher order thinking, either by facilitating student’s interaction with complex knowledge or engaging them in demanding cognitive processes. By analysing selected examples, we found that the relationship between knowledge and processes was not linear: it seems possible to have a cognitively demanding task with little knowledge, and simple tasks performed on complex knowledge. We argue for using a two-dimensional model that captures cognitive processes as well as different types of knowledge required.